Inclusive Language in Student Writing: Awareness and Innovation - Ahmed, Khawlah; McCarthy, Philip; Kaddoura, Noor; Thomas, Anuja; Al-harthy, Ayah (Advances in Social Sciences Research Journal, 2022)
The goal of inclusive language is to replace terms and phrases that may cause offense or denigrate a particular group of people. One of the major issues stymieing a broader application of inclusive language is simply awareness, especially for those who speak English as an additional language. Given that few places focus on wording issues more than the writing classroom, it is surely there that instruction and its associated Automated Writing Evaluation tools need to make appropriate contributions. Accordingly, this paper assesses faculty, student, and technology for their respective current levels of awareness. The results of our study suggest that both faculty and students appear to be inconsistent and lacking in awareness on many issues of inclusive language. Meanwhile, our analysis suggests technology appears to have many opportunities to both improve and increase its role in assisting with a greater understanding and application of inclusive language.